Prevalence of ocular trauma and barriers to use of personal protective devices among welders in Hetauda, Nepal - Sunil Thakali; Mohini Shrestha; Aleena Gauchan; Dikshya Bista; Hom Bahadur Gurung (PLoS ONE, 2025)
Introduction Welding poses significant ocular hazards in Nepal’s industrial settings; however, data on trauma prevalence and protective barriers remain limited. This study assessed the burden of ocular trauma, personal protective equipment (PPE) practices, and associated risk factors among welders in Hetauda, Nepal. Methods This cross-sectional study conducted in 2024 included 111 welders in Hetauda. Participants underwent comprehensive eye examinations and structured interviews. Logistic regression was used to assess factors associated with ocular trauma. Results The prevalence of ocular trauma was 62.16%, primarily caused by metal chips (60.87%) and flames (37.84%). Although 78.39% of welders reported using PPE, 72.97% relied on non-certified sunglasses, and only 1.80% used certified protective goggles. Key barriers to appropriate PPE use included the absence of workplace mandates (62.50%) and a belief that protection was unnecessary (64.52%). Significant risk factors for trauma included male gender, lack of safety training (43.48%), and age between 46 and 60 years. Common ocular morbidities were corneal opacity (20.72%) and conjunctival congestion (10.36%). Conclusions Despite reported PPE usage, the continued high rate of ocular trauma highlights deficiencies in equipment quality and training. Mandating certified eye protection, enforcing workplace safety policies, and integrating occupational health education are critical steps for preventing eye injuries in Nepal’s industrial sector.